Tantangan Dan Peluang Pembelajaran IPS Materi Keragaman Sosial Dan Budaya Di Indonesia Pada Siswa Kelas 4 Sekolah Dasar - Handayani, Christiana Switaningsih (Pena Edukasia, 2024)
The 21st century learning paradigm states that Social Science Education in elementary schools, especially social and cultural diversity materials in Indonesia, plays an important role in instilling in students the character of love for the homeland. However, learning in this material faces various challenges. This study aims to look at the challenges and opportunities of social studies learning material on social and cultural diversity in Indonesia in grade 4 elementary school students using  the literature review method. This literature study was carried out by analyzing several research articles from 2019 -2024. Data was obtained from Google Schoolar with the keywords challenge; opportunity; social and cultural diversity; primary school. The results of this literature study provide advice to primary school teachers to develop and adapt diverse and representative learning materials, which include ethnic, cultural, and religious diversity in Indonesia. In addition, teachers also need to apply innovative and interactive learning approaches, such as group discussions, role-playing games, or collaborative projects, to increase student engagement in learning about social and cultural diversity. Furthermore, teachers are also expected to be able to utilize technology such as multimedia presentations, online learning platforms, or interactive applications to present information about social and cultural diversity in an interesting and interactive manner. Thus, the results of this research are expected to provide input for teachers, schools, and other stakeholders in an effort to improve the quality of social studies learning materials for social and cultural diversity in Indonesia.